Pemikiran Hadis Muhammad Al-Ghazali Dan Implikasinya Terhadap Tasyri` (Analisis Terhadap Kitab As-Sunnah An-Nabawiyyah Baina Ahl Al-Fiqh Wa Ahl Al-Ḥadīṡ) - Hafiz, Maulana; Anwar, Husnel; Is, Fadhilah (SHAHIH (Jurnal Ilmu Kewahyuan), 2023)
Muhammad al-Ghazali, a prominent hadith scholar from Egypt, is widely known as a leading figure in modern times. One of his significant contributions to the field of Hadith studies is a book entitled "as-Sunnah an-Nabawiyyah baina Ahl al-Fiqh Wa Ahl al-Ḥadīṡ," which focuses on critical analysis of Hadith. The aim of this research is to explain Muhammad al-Ghazali's views on the development of the methodology for understanding hadith, as well as to examine the consequences arising from his interpretation of tasyri`. This research uses content analysis methodology, specifically utilizing library research techniques to examine Muhammad al-Ghazali's hadith ideas and their relevance to tasyri` in his written works on hadith. This research adopts an empirical rationality approach. From this research the author found several findings, namely; First, Muhammad al-Ghazali in his book has created a dichotomy between Hadith Experts and Fiqh Experts. He said that only Fiqh experts are more proportional in detecting the authenticity of a Hadith. This has a negative impact on Hadith experts where they are accused of being a textual group in understanding Hadith. Second, the individual expressed his reluctance to utilize Hadith aḥad as a means of upholding his faith. According to an individual's point of view, topics related to faith should be based on personal beliefs and not on speculative reasoning, because speculative reasoning is less useful in terms of practical application and application of the law. This has implications for the Hadiths regarding events surrounding the Day of Judgment, including the signs, events of the Day of Judgment and events of the Day of Resurrection to the issue of heaven and hell. All this is narrated by Hadith aḥad. Third, in carrying out criticism, he focuses on matan criticism rather than sanad criticism. In the context of scientific investigation, examining the validity of a hadith and explaining its intended meaning, with the aim of understanding the teachings conveyed by the Prophet.